Evaluation of Knowledge and Confidence following Opioid Overdose Prevention Training: A Comparison of Types of Training Participants and Naloxone Administration Methods. Issue 1 (January 2016) - Ashrafioun, Lisham; Gamble, Stephanie; Herrmann, Michele; Baciewicz, Gloria
Background: The purpose of the current study was to assess the effect of opioid overdose prevention training on participants' knowledge about opioid overdose and confidence to recognize and respond to opioid overdose situations as a function of naloxone administration (i.e., injection vs. intranasal spray) and participant type (friend/family, provider, "other"). Methods: Opioid overdose prevention trainings were offered throughout a mid-sized metropolitan area in the northeast. Participants ( n = 428) were trained to administer naloxone via intramuscular injection ( n = 154) or intranasal spray ( n = 274). All training participants were given pre-post assessments of knowledge about opioid overdose and confidence to recognize and respond to opioid overdose situations. Results: Participants' overall knowledge and confidence increased significantly from pre- to post-training ( p s < .001). There was no significant association between knowledge and route of administration or participant type. Knowledge significantly increased from pre- to post-training in all participant types ( p s < .001). Confidence improved significantly from pre- to post-training across both routes of administration ( p s < .001). However, confidence was higher among those who were trained using the intranasal naloxone compared to those who were trained using the intramuscular injection naloxone at pre- ( p = .011) and post-training ( p < .001). Confidence increased from pre- to post-training in each of the participant types ( p s < .001). Post-hoc tests revealed that confidence was higher among providers and friends/family members compared to "other" participants, such as first responders, only at post-training ( p < .05). Conclusions: Opioid overdose trainings are effective in increasing knowledge and confidence related to opioid overdose situations. Findings suggest that trainees are more confident administering naloxone via intranasal spray compared to injection. Future research should attempt to identify other factors that may increase the likelihood of trainees' effectively intervening in opioid overdose situations.